Ethical and Unethical Practices Within the Food Supply Chain: Exploring the Role and Application of Blockchain Technology - Melanthiou, Yioula; El Naddaf, Sami; Efthymiou, Leonidas; Christodoulou, Klitos (My University, 2024)
Many countries globally are experiencing food crises due to a combination of factors that require external support to address any critical problems with food insecurity. In addition, many countries in the MENA region engage in unethical practices in the food supply chain, including Jordan, Palestine, Turkey, Cyprus, and Saudi Arabia. Unethical practices range from bribery to corruption, defects, and food fraud. Different factors play a critical role in food production. For example, animal welfare, customer and employee safety and protection, the use of natural resources, the country’s raw materials in terms of quality and safety, the global trade between buyers and suppliers, and the changes in temperature that affect crops. In an example of food fraud, Trudel and Cotte (2009) stated that consumers preferred ethical products over unethical ones and were willing to pay for them even though they were more expensive. Any misconduct or unethical behavior will disrupt the relationship between buyers and suppliers, indicating that some members of the supply chain were responsible for this illegal or unethical act. As stated by Kaynak et al. (2015), the buyers blame salespeople for faulty or defective products; however, the main problem rests with the suppliers, since they are responsible for assembling the raw materials and distributing the products to the market. Therefore, it is essential to control all the processes from the point of origin to the end consumers. Even though a code of ethics is beneficial and useful for companies, it is not a guarantee that they will implement ethically responsible behavior in the marketplace (Nijhof et al., 2003). Companies such as Enron, Worldcom, Arthur Andersen, and Parmalat destroyed their market reputations by engaging in unethical behaviors, leading to dire situations. In addition, several firms, such as Skandia and Systembolget, were accused of bribery and ethical violations (Dibra, 2016). Companies must emphasize the importance of developing their managers’ ethical decision-making skills in order to resolve ethical issues in supply chains. Therefore, greater effort should be dedicated to establishing norms that encourage ethical judgments. Furthermore, in-house ethical training programs could be useful in the future, particularly if rewards and benefits are offered to managers, so that they could act or judge ethically with a reduction in unethical practices (Ha & Nam, 2014). Companies engaging in unethical practices affect supply chain relationships, compelling firms worldwide to prioritize business ethics as a critical strategic action (Ha & Nam, 2016). When making ethical decisions, values and judgments are regarded as crucial variables based on the circumstances of the specific situation (Ferrel et al., 2011). With the rapid advancement of information technology and the emergence of internet-based ecommerce, enterprises began to focus on improving the supply chain’s performance and the strategic partner relationship of the supply chain network (Cui, 2018). The food technology sector is constantly changing, with new advances and breakthroughs every year. Advances in technology and industrialization may give consumers the opportunity to increase their knowledge about food producers and the quality of the product through the labels found on them. Nowadays, no one can deny the presence and importance of Blockchain technology in different fields especially in the food industry. As a distributed digital ledger technology, the blockchain technology works as a "peer to peer" distributed data infrastructure that can be used for recordkeeping and the transfer of value, with potential applications in multiple sectors including for supply chain management and logistics. In the agri-food supply chain, the blockchain technology shows promise for ensuring traceability and transparency of product information as fundamental differentiators (Kim et al. 2019). While the relationship between blockchain technology and supply chains have been widely investigated (Treiblmaier, 2018), the research on the application of blockchain technology in food supply chain is still at the embryonic stage especially when it comes to ethical practices. The main gap in this study is the lack of concrete exploration into the specific applications of blockchain technology in addressing ethical issues within the food supply chain. Additionally, how exactly blockchain can be utilized to mitigate unethical practices such as bribery, corruption, defects, and food fraud, requires further investigation. Therefore, there is a need for further research to bridge this gap by conducting comprehensive studies that explore the practical implementation of blockchain technology to promote ethical practices in the food supply chain industry. Regarding the methodology, an analysis of the existing literature will take place to establish a foundational understanding of ethical issues within food supply chains and the potential of blockchain technology to address them, followed by a gathering of the primary data through semi-structured interviews with different food firms from the MENA region countries, alongside secondary data from reports, publications, and industry sources, to enrich the study with diverse perspectives and empirical evidence. Thus, developing a framework for evaluating the ethical implications of blockchain implementation in food supply chains, ensuring a systematic approach to assessing its impact on ethical standards, designing a strategic plan for integrating blockchain solutions into food supply chains, and outlining practical steps for leveraging blockchain to address identified ethical challenges effectively, is critical in this research. This abstract intends to explore the potential applications of blockchain-based technology to agri-food supply chains, its benefits and limitations, especially in deploying ethical practices and reducing unethical practices in the food supply chain industry. In other words, the study aims to explore how blockchain technology can enhance traceability and transparency of product information, ultimately improving the ethical standards of food production and distribution. Additionally, it intends to suggest approaches to overcome challenges associated with implementing blockchain technology in this context. As for the contributions, the abstract, mainly the research will contribute in exploring the potential of blockchain technology in agri-food supply chains, emphasizing its role in promoting ethical practices: it provides insights into how blockchain can enhance traceability and transparency, thereby improving ethical standards in food production and distribution; by identifying both benefits and limitations, the abstract offers practical guidance for researchers, policymakers, and industry stakeholders. Furthermore, it suggests approaches to overcome challenges associated with implementing blockchain technology, encouraging further research in this under-investigated area. Overall, this research contributes to advancing the knowledge and understanding of how emerging technologies like blockchain can be leveraged to address ethical issues within the food supply chain industry.
Keywords: Ethical Practices; Unethical Practices; Blockchain Technology; Food Supply Chain; Technology; Food Fraud Consumer Behavior